The worth of art : financial tools for the art market - Cifuentes, Arturo; Charlin, Ventura (Columbia University Press, 2023)
"In recent years the art market has grown in both size and importance. It is currently estimated that ultra-high-net-worth individuals (UHNWIs) maintain 6% of their holdings in art-related assets; thus, at least US$ 1.75 trillion are invested in art worldwide. This figure does not take into account the holdings of museums, banks, endowments, insurance companies, and other institutional investors. Artistic objects, notwithstanding their aesthetic merits, can also be valuable financial assets. This book shows readers with finance backgrounds how to use the analytical tools employed in more conventional markets (stocks, bonds, real estate) to assess the risk and rewards associated with participating in the art market as an investor, collector, banker, insurer, lender, auctioneer, speculator, etc. The book demonstrates the use of data analytics and statistics for art valuation vs. subjective appraisal based on connoisseurship"-- Provided by publisher.
Keywords: Art -- Valuation -- Handbooks, manuals, etc.; Art appreciation -- Handbooks, manuals, etc.; Art -- Appréciation -- Guides, manuels, etc.; Art -- Évaluation -- Guides, manuels, etc.; Art -- Valuation; Commodities.; Investments & Securities.; BUSINESS & ECONOMICS.; Financial Risk Management.; Finance.; ART.; Handbooks and manuals; Electronic books.